Macromolecular and Micronutrient Profiles of Sprouted Chickpeas to Be Used for Integrating Cereal‐Based Food. Issue 1 (12th September 2016) - Marengo, Mauro; Carpen, Aristodemo; Bonomi, Francesco; Casiraghi, Maria Cristina; Meroni, Erika; Quaglia, Lucio; Iametti, Stefania; Pagani, Maria Ambrogina; Marti, Alessandra
Abstract : Pulse flour may be used to improve nutritional traits of gluten and gluten‐free formulations in traditional food such as bread or pasta. However, owing to some intrinsic nutritional, textural, and sensory properties, the use of pulses as ingredients for production of enriched food remains limited. In this study, we investigated the modification in macromolecules and micronutrients in industrial‐scale flour from partially sprouted chickpeas to define its possible use as an ingredient in cereal‐based foods. Controlled sprouting resulted in significant decrease of antinutritional compounds (e.g., phytic acid and serine protease inhibitors) and in an increase of free minerals and vitamins. Sprouting also affected the overall structural organization of proteins (such as aggregate formation) and their thiol/disulfide balance, and it promoted release of peptides. All of these had a positive effect on dough mixing properties, in particular for dough development. Formulations with enrichment in sprouted chickpea flour (wheat/chickpea ratio = 100:20) were tested also as for their dough leavening properties, which improved with respect to flour from nonsprouted chickpeas. Taking into account the modifications induced by partial sprouting on an industrial scale, we can conclude that sprouted chickpea flour represents an interesting ingredient for production of enriched cereal‐based food with better nutritional and rheological characteristics.